Intermolecular Trapping of Alkoxyl Radicals with Alkenes: A New Route to Ether Synthesis - Barthelemy, Anne-Laure; Tuccio, Béatrice; Magnier, Emmanuel; Dagousset, Guillaume (Synlett, 2019)
Alkoxyl radicals are highly reactive species which rapidly react by hydrogen atom transfer (HAT) or β-fragmentation to afford a carbon-centered radical. We discuss herein how these RO· radicals can be efficiently trapped in an intermolecular manner by styrene derivatives when they are generated by photoredox catalysis from the corresponding N-alkoxypyridinium salts. This allows for the synthesis of valuable ethers with complete anti-Markovnikov regioselectivity.1 Introduction2 Anti-Markovnikov Alkoxylation of Alkenes: Background3 Addition of Alkoxyl Radicals to Styrenes4 Summary and Outlook
Keywords: ether synthesis; photoredox catalysis; alkoxyl radicals; anti-Markovnikov addition; alkenes; N-alkoxypyridinium